Adjunctive Application of Systemic Antibiotics in Non-surgical Aggressive Periodontitis Treatment: Clinical and Microbiological Findings - Milinkovic, Iva; Mijailovic, Iva; Markovic, Aleksa; Janjic, Bojan; Nikolic, Nadja; Milasin, Jelena; Milicic, Biljana; Aleksic, Zoran; Vasovic, Dina (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Aggressive periodontitis (AgP) is associated with an extensive and rapid destruction of periodontal tissues. Unpredictable treatment outcomes of the disease are consequences of various cross-linked factors. Antimicrobial adjunctive treatment is routinely used as a part of non-surgical periodontal treatment (NSPT) of AgP. AIM: Therefore, the aim of this study was to compare the effects of active periodontal treatment (APT) combined with systemic antibiotics with mechanical debridement alone, in patients with generalized AgP (GAgP). METHODS: Two groups, consisting of 10 participants each, were randomly formed. Both groups were clinically and microbiologically tested and monitored for 3 months. Test group received APT with antimicrobial supplementation (amoxicillin and metronidazole [AMX-MET]). Patients from the control group were treated by APT only. Clinical and microbiological parameters were recorded at baseline and 3 months following the NSPT. Clinical measurements involved probing depth, clinical attachment level, bleeding on probing, and plaque index. Samples of subgingival crevicular fluid were analyzed by qualitative polymerase chain reaction. RESULTS: Significant improvement of all clinical parameters was observed 3 months following the NSPT (p < 0.05), but significant difference between groups was not found (p > 0.05). Periodontal pathogens’ detection between baseline and 3 months follow-up was also not statistically significant in both examined groups (p > 0.05). CONCLUSION: Similarity of results obtained in both treatment groups underlined the key role of APT in the treatment of AgP. The AMX-MET supplementation did not improve clinical and microbiological outcomes, when compared to APT alone. Longer follow-up period, with larger sample, could provide a more comprehensive insight into this issue.